2014
DOI: 10.5603/cj.a2013.0109
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between glycemic control and BNP levels in diabetic patients

Abstract: (Cardiol J 2014; 21, 3: 252-256)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Data demonstrated a positive correlation between BNP and HbA1c (r=0.345, p= 0.003). 15 This finding is consistent with ours as our data also showed a positive correlation between two variables in the diabetic group, which is independent of BMI. Thus, diabetic patients have higher NT-proBNP levels as compared to non-diabetics.…”
Section: Discussionsupporting
confidence: 93%
“…Data demonstrated a positive correlation between BNP and HbA1c (r=0.345, p= 0.003). 15 This finding is consistent with ours as our data also showed a positive correlation between two variables in the diabetic group, which is independent of BMI. Thus, diabetic patients have higher NT-proBNP levels as compared to non-diabetics.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the levels of hs-Tnl and BNP are closely correlated with each other after myocardial infarction, and high levels of troponin may reflect the severity of heart failure [43]. Second, this may be due to factors such as renal impairment and hyperglycemia that contribute to both elevated hs-Tnl and BNP in patients with T2DM [44, 45]. Nevertheless, recent studies demonstrated that perioperative glycemic control with exenatide infusion does not affect troponin and BNP release after cardiac surgery [46].…”
Section: Discussionmentioning
confidence: 99%
“…The active form, BNP(1–32), is degraded by DPP4 by removing the two N-terminal amino acids (serine and proline) to produce BNP(3–32), which has reduced biological activity. Elevated levels of NPs were proved in hyperglycemia and decrease by improved glycemic control (Dal et al 2014 ). However, in cardiac pathology, it seems that DPP4 is implicated in high levels of NPs as it was found that genetic deletion of DPP4 improved the elevated levels of ANP and BNP in rats subjected to myocardial ischemia/reperfusion (Ku et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%